Konstruksi Moderasi Beragama dalam Gerakan Jamaah Tablig Kota Palopo - Andi Asraf; Baso Hasyim; Muhammad Ilham (Pustaka Digital Indonesia, 2025)
The urgency of this research lies in understanding how the construction of religious moderation is formed within the Jamaah Tabligh movement in Palopo City, considering the importance of moderation in maintaining religious harmony in a pluralistic society. This study explores the perceptions of the Jamaah Tabligh movement regarding the concept of religious moderation and its implications for their da'wah (Islamic preaching) activities. The research employs a descriptive qualitative method using an ethnographic approach. Data were collected through observation, interviews, and documentation, and then analyzed through description, analysis, and interpretation. The findings reveal that most members of the Jamaah Tabligh had never heard of the term